Experimental and Numerical Modelling of Turbulent Flow over an Inclined Backward-Facing Step in an Open Channel - Prihoda, Jaromir; Zubik, Pavel; Sulc, Jan; Sedlar, Milan (Communications - Scientific letters of the University of Zilina, 2012)
The contribution deals with the experimental and numerical modelling of the turbulent flow over an inclined backward-facing step in an open water channel. The modelling was carried out in the wide range of the Froude number covering the subcritical, supercritical and near critical regimes as well. The study was concentrated particularly on the development of flow separation and on changes of free surface. Numerical results obtained using the commercial software ANSYS CFX 12.0 for the two-equation SST model and the EARSM model were compared with experimental data obtained by means of PIV and LDA measuring techniques.